2007
DOI: 10.1111/j.1365-4632.2007.03418.x
|View full text |Cite
|
Sign up to set email alerts
|

Myxoinflammatory fibroblastic sarcoma – report of a rare case at an unusual site with review of the literature

Abstract: We report a case of myxoinflammatory fibroblastic sarcoma in a thirteen year old girl who presented with a tender swelling in the left upper back. The tumor consisted of varying proportions of inflammatory, myxoid and hyalinized areas. Large bizarre cells with virocyte like inclusions and lipoblast like cells were present. To the best of our knowledge this is the first reported case of myxoinflammatory fibroblastic sarcoma of the back, the extremities being the commonest site of involvement. Due to its varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Although myofibroblastic lesions account for about 12% of pediatric soft-tissue tumors in children, fewer than 10 MIFS have thus far been reported in childhood (Table 2) [1,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Although myofibroblastic lesions account for about 12% of pediatric soft-tissue tumors in children, fewer than 10 MIFS have thus far been reported in childhood (Table 2) [1,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Tenosynovitis, ganglion cyst, and myxoma (for the inflammatory and benign entities), and myxoid malignant fibrous histiocytoma, myxoid liposarcoma, and epithelioid sarcoma (for the malignant tumors) are the main components of the histopathological differential diagnosis of a giant cell tumor in the tendon sheath or of a myxoid origin [2,5]. Because of the difficulty of an accurate diagnosis from the lesion's clinical presentation or radiological characteristics, the diagnosis is often delayed and a surgical excision is more likely to be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Premalata et al [5] reported upon a MIFS of the upper back, over the scapula. They performed a wide excision of the tumor, without rib resection, and reported no recurrence within 10 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports had suggested that myxofibrosarcoma is a difficult and important differential diagnosis of MIFS 2,4,5 . Histopathologically, however, myxofibrosarcoma and MIFS shared some feature with each other, such as various proportions of myxoid components and pleomorphic spindle/stellate cells in a myxoid background 5,6 .…”
mentioning
confidence: 91%
“…Myxofibrosarcoma usually presents with markedly infiltrative growth but also can have a multinodular growth pattern, like MIFS 3 . MIFS is characterized by the presence of a myxoid matrix that contains inflammatory cells and variable, enlarged, atypical cells, including RS‐like cells, spindle/epithelioid cells, ganglion‐like, lipoblast‐like cells and bizarre giant cells 4–6 . Although pseudolipoblasts and multinucleated giant cells with ample cytoplasm can be seen in myxofibrosarcoma, it lacks the large ganglion/RS‐like cells of MIFS 6 .…”
mentioning
confidence: 99%